NILAI RELIGIUS DALAM NOVEL THE HAZE INSIDE KARYA AIU AHRA DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA DI SMA - Zilly Amelia Ifada; Dodi Firmansyah; Ilmi Solihat (Universitas Batanghari, 2026)
This research is motivated by deviant behaviour that is still widely found, especially among teenagers. Based on these problems, the purpose of this study is to describe the religious value in the novel The Haze Inside by Aiu Ahra and the implication for Indonesia Language learning in high school. The method used is descriptive qualitative, with data collection techniques in the form of careful observation and note-taking techniques. The results showed the existence of religious values in the novel The Haze Inside by Aiu Ahra, including: aspects of faith (tauhid), including faith in Allah, and piety to Allah; aspects of life norms (fiqh), including haram, makruh, and sunat; and aspects of behavioral attitudes (morals), including tawakal, honesty, and discipline. This study also shows that the novel The Haze Inside by Aiu Ahra can be utilized as teaching material in Indonesian language learning because it meets the criteria for ideal teaching material selection, namely language aspect, psychological, and cultural background.